The Relationship Between Duolingo Usage Intensity as Reinforcement and Vocabulary Mastery and Learning Motivation of Junior High School Students - Fadly Uzzaki; Zuwirna; Jasrial; Rahmi Pratiwi (Postgraduate, University of Mataram, 2026)
This study aims to evaluate the effectiveness of Duolingo as a reinforcement activity and analyze the relationship between objective and subjective usage intensity, vocabulary mastery, and learning motivation. Utilizing a quantitative approach with a correlational design, data was collected from 21 Junior High School students selected via purposive sampling. The instruments included digital logs from Duolingo for Schools, pretest-posttest vocabulary assessments, and questionnaires, which were analyzed using the Wilcoxon Signed Rank Test and Spearman Rank Correlation. The results demonstrated a significant increase in vocabulary mastery, achieving a medium N-Gain of 0.29, alongside high, predominantly intrinsic learning motivation with a mean score of 3.48. However, the discussion reveals a distinct